Effect of varying dietary crude protein and metabolizable energy levels on leg abnormalities and performance in broiler chickens - Rodríguez-Ortega, Leodan T; Rodríguez-Ortega, Alejandro; Mera-Zuñiga, Fredy; Pro-Martínez, Arturo; Hernández-Guzmán, Filogonio J; Sosa-Montes, Eliseo; González-Cerón, Fernando; Leyva-Jimenez, Hector (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Nutrient restriction is a common strategy to prevent metabolic disorders in fast growing broiler chickens, but limited information is available regarding the impact of diets with low protein and energy on leg abnormalities. Objective: Two experiments were conducted to evaluate the effect of varying crude protein (CP) and metabolizable energy (ME) levels on gastrocnemius tendon (GTeBS) and tibia breaking strength (TiBS), gait score (GS) and valgus/varus angulation (VAng). Methods: In Experiment 1, eight-d-old Ross 308 broilers (n=90) were randomly assigned into three treatments: 13/2,900 (13% CP and 2,900 kcal ME kg-1 of diet), 17/3,000 (17% CP and 3,000 kcal ME kg-1 of diet), and 21/3,025 or control (21% CP and 3,025 kcal ME kg-1 of diet). In Experiment 2, six-d-old Ross 308 chickens (n=192) were randomly distributed into two treatments: 16/3,000; 16% CP and 3,000 kcal ME kg-1 of diet and 21/3,000 or control; 21% CP and 3,000 kcal ME kg-1 of diet. In both experiments data were analyzed as one-way ANOVA. Results: In Experiment 1, broilers in the 17/3,000 and control treatments had similar (p>0.05) GTeBS (202 and 224 N, respectively), and TiBS (338 and 332 N, respectively). Birds in the 13/2,900 treatment showed higher GS (lower walking ability; 80% of birds with score >3), and greater VAng (53% of birds with score >2) than broilers in the control treatment (0% of birds with GS score >3 and 0% of birds with VAng score >2). Experiment 2, broilers in the 16/3,000 showed similar VAng, GS and TiBS than birds in the control treatment. However, birds in the 16/3,000 treatment showed lower (-26%) GTeBS than birds in the control treatment (p<0.05). Conclusions: Feeding broilers with 16% CP and 3,000 kcal ME kg-1 of diet did not affect tibia breaking strength, gait score and valgus/varus angulation. A diet containing 16% CP or less and 2,900-3,000 kcal ME kg-1 reduces tendon and tibia breaking strength.